Varieties of demand and growth regimes: Post-Keynesian foundations - Eckhard Hein (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2022)
We review post-Keynesian contributions to demand and growth regime analysis. First, we distinguish the Kalecki-Steindl approach and the Sraffian supermultiplier approach as relevant theoretical foundations for demand and growth regime research, with investment-driven and distribution-led growth in the focus of the former and autonomous demand-led growth in the latter. Based on this, we review different ways of analysing the co-existence of demand and growth regimes in the current period of neoliberal and finance-dominated capitalism. We distinguish, first, a basic national income and financial accounting decomposition approach, second, a Sraffian supermultiplier inspired growth decomposition approach, and, third, several lenses looking at growth drivers. We argue that these three levels of analysis are, in principle, not mutually exclusive nor even contradictory, but that they rather complement each other. We conclude that, in particular the PK analysis of growth drivers provides several systematic links with comparative and international political economy approaches, when it comes to the introduction of the political economy dimension (social blocs, growth coalitions, changes in institutions favouring certain type of re-distribution and economic policies, etc.), while the national income and financial accounting, as well as the Sraffian supermultiplier growth accounting decomposition approaches provide the consistent macroeconomic foundations for such syntheses.
Keywords: B59; E02; E11; E12; E65; P51; 330; Demand and growth regimes; post-Keynesian economics; Kalecki-Steindl models; Sraffian supermultiplier models; wage-/profit-led regimes; finance-led/finance-burdened regimes; debt-led private demand boom regimes; export-led regimes; domestic demand-led regimes